Breaking the Legal Glass Ceiling in ‘Gender Equal’ Finland - Alaattinoğlu, Daniela (Helsingin yliopisto, 2026)
Who are the senior producers of legal knowledge and senior legal practitioners in Finland? Inspired by recent international scholarship on the people behind the law and glass ceilings in academia and the legal profession, this chapter investigates the gender balances in three high-level sites of legal knowledge production and practice: i) the Finnish Supreme Courts, ii) the professors working at Finnish law schools, and iii) the partners of major law firms in Finland. In the Finnish context, the text continues the discussion initiated by Johanna Niemi and Daniela Alaattinoğlu on the gendered legacy of Finnish law and its implications for today’s Finnish legal scholarship and education, posing the question of why discussions on gender and representation—while women increasingly enter legal professions—are still underdeveloped and contested in a country which claims to already be ‘gender equal’.
The Neutral Law? Essays in Honour of Johanna Niemi